Implementasi Model Cooperative Learning Tipe Jigsaw dan STAD Bebasis HOTS Pada Pembelajaran Matakuliah Bimbingan Belajar Program Studi Pendidikan Bimbingan Konseling FIP-Unima - Meisie L. Mangantes (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to analyze, design and develop a Jigsaw and STAD-based Coopreative Learning Model based on HOTS (Higher Order Thinking Skills). The research method is using a quantitative approach with the experimental method. Subjects and objects of research are lecturers and students of the Guidance and Counseling Study Program, Faculty of Education, Manado State University. Data was collected through tests, observations, interviews, and documentation as well as literature study. The targeted outputs in this research are: Model Design and International Article Publication